Desarrollo De Un Sistema Continuo Para La Producción De Metano Y Biofertirrigación Basado En Cultivo De Microalgas Para El Reciclaje De Nutrientes (2025)
Microalgae have been widely considered as potential feedstock for fuels, fertilizers, chemicals, wastewater treatment and other products with added value. In this work, a continuous methane production and biofertilization system is developed using an airlift photobioreactor, where microalgae are cultivated by recycling nutrients from wastewater such as urine, since its composition contains nitrogen, phosphorus and potassium that can be used for the production of microalgal biomass, as an energy source and biofertilizer. A UASB bioreactor is configured attached to a laboratory scale photobioreactor or PBR for methane production.